Assessing genetic diversity among spontaneous mutant progenies of lentil (Lens culinaris) variety DPL 62 - YADAV, SUNAINA; YADAV, RAJESH; RAVIKA,; SINGH, VIKRAM JEET; SAMITA, (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted during winter (rabi) season 2017–18, at the Department of Genetics and PlantBreeding, CCS Haryana Agricultural University, Hisar, Haryana, to assess the genetic divergence for yield and yieldcomponent among 60 spontaneous mutant lines of lentil (Lens culinaris Medikus ssp. culinaris). Hierarchical clusteranalysis grouped maximum numbers of genotypes in cluster II. Maximum intra cluster distance was exhibited by cluster II followed by cluster IV and cluster III whereas, maximum inter cluster distance was observed between cluster III and cluster VI followed by cluster V and cluster VI and cluster I and VI. Based on the high yield and yield contributing traits and their presence in distant clusters, the genotypes, viz. RKL 61F-2-15, RKL 58F-3715, RKL 1003-68G, Garima, RKL 1003-69G-A, RKL 23C-2741A and RKL 26C-345 can be effectively used in hybridization programmefor lentil improvement to obtain desirable segregants. The first six principal component (PC) explain more than 65%of the total variability. Based on Principal factor (PF) scores, genotypes RKL 3-94, RKL 26C-340, RKL 50E-273,RKL 73GIII-13, RKL 51E, RKL 23C-2741 and RKL 26C-345 can be regarded as early maturing and high yielding.Genotypes, viz. RKL 61F-2-15, RKL 58F-3715, RKL 1003-68G, Garima, RKL 1003-69G-A, RKL 23C-2741A andRKL 26C-345 belongs to diverse clusters can be considered as better parents to be used in hybridization programme.